Assessing the Development of Emotional and Communicative Competence in Medical Students: Longitudinal Research (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The purpose of this study is to assess the development of emotional and communicative competence of medical students in the process of their education. Emotional and communicative competence are critical skills for healthcare professionals as they provide effective patient communication, empathy and cultural competence that are critical to providing high quality patient care.